Harsh lessons Iraq, Afghanistan and the changing character of war - Barry, Ben (Retired brigadier) (Adelphi (Series) (International Institute for Strategic Studies), 2017)
"Launched in the wake of 9/11, the US-led interventions in Afghanistan and Iraq forced painful transformations in Western militaries. As successful regime-change operations gave way to prolonged insurgencies, these forces confronted wars whose character rapidly developed in unanticipated directions. The US and its allies repeatedly failed to align national ends, ways and means to achieve stabilisation, reconstruction and political progress in Afghanistan and Iraq, before rediscovering counter-insurgency principles established in previous conflicts. The lessons of the wars are likely to continue shaping Western states' approach to intervention and warfare for years to come. This Adelphi book examines the military evolution of the conflicts, and their implications for the future character of war. It shows why combat remains the core military capability, and explains successful and unsuccessful adaptation by armed forces, especially the essential roles of leadership, culture and organisational agility in promoting 'learning under fire'. Written by the author of the British Army's report on post-conflict stabilisation in Iraq, the book is a valuable guide for policymakers, government officials, military officers and scholars seeking to understand the military legacy of a contentious and unpopular chapter in Western strategy." --Back cover